2017
DOI: 10.1016/j.conbuildmat.2016.12.132
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of the negative effects of recycled aggregate water absorption in concrete technology

Abstract: The widespread use of natural aggregates in construction activities, together with the global population increase, gave rise to a depletion of this natural resource and to a progressive increase of its transport distances. On the other hand, the construction and demolition wastes (C&DW) resulting from the construction activities are often deposited in landfills and city outskirts, causing environmental and social problems, such as erosion, deforestation, water contamination and human conflicts. The reuse of C&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 25 publications
(40 reference statements)
2
28
0
Order By: Relevance
“…Rougher shape of recycled aggregates (RA) compared to virgin aggregates (VA) causes some changes in workability. According to the research work by Eckert and Oliveira [1], even if recycled materials are pre-saturated, there is a potential in workability reduction due to the high shape index of recycled materials. Mas et al [13] observed that slump decreased 66% by 50% replacement of RA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rougher shape of recycled aggregates (RA) compared to virgin aggregates (VA) causes some changes in workability. According to the research work by Eckert and Oliveira [1], even if recycled materials are pre-saturated, there is a potential in workability reduction due to the high shape index of recycled materials. Mas et al [13] observed that slump decreased 66% by 50% replacement of RA.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, the amount of construction solid wastes has increased and municipalities and local governments have faced environmental problems due to lack of land to dispose them. On the other hand, most of the landfills are often in the outskirts of the cities [1] and a large portion of construction debris is dumped near roads and rivers in an uncontrolled way. Not only does this create ugly landscapes, but it also intensifies underground water and soil pollution, deforestation, erosion, and the flood hazard in the region.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have explored various approaches and techniques to reduce or partially compensate the detrimental effects of RCA, or to improve the characteristics of the resultant concrete. These approaches include adjusting and trialing different mixing methods, materials and processes, such as varying the water/cement (W/C) ratio (Eckert and Oliveira 2017;Pandurangan et al 2016;Saravanakumar and Dhinakaran 2012), blending RCA with NA at various replacement ratios (Abdel-Hay 2015; Haghighatnejad et al 2016;Yang et al 2011), as well as cement coating (Binyu and ChiSun 2015;Martirena et al 2017;Tam et al 2005). Likewise, the properties of RCA can be improved by undertaking several quality improvement treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, these activities in large cities have grown dramatically due to the increase in population, producing a greater demand for land and the need to have urban areas with large areas. This situation has generated an increase in the amount of solid construction waste, which leads to the existence of environmental problems that must be addressed by the municipalities and regional governments, through the control and distribution of land destined as landfills [2]. Due to the lack of these for construction, construction companies choose to dispose of their waste in nearby places to avoid higher expenses, which causes unpleasant impacts on the landscape, underground water and soil pollution, deforestation, erosion and a major food hazard to surrounding areas; As a solution, it is proposed to use recycled concrete aggregates from the demolition of structural elements in the manufacture of concrete to help preserve natural resources and promote their sustainability [3], as well as the development of sustainable construction.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of these for construction, construction companies choose to dispose of their waste in nearby places to avoid higher expenses, which causes unpleasant impacts on the landscape, underground water and soil pollution, deforestation, erosion and a major food hazard to surrounding areas; As a solution, it is proposed to use recycled concrete aggregates from the demolition of structural elements in the manufacture of concrete to help preserve natural resources and promote their sustainability [3], as well as the development of sustainable construction. According to [2] that recycled aggregates have a rougher texture than natural aggregates and this causes some changes in workability, even if recycled materials are pre-saturated, resulting in reduced workability due to the high rate of Form of recycled materials. The authors of [4] found that the content of hardened cement in the recycled aggregate is greater than in the natural aggregate, the water absorption of the recycled aggregate is greater, and its yield is lower.…”
Section: Introductionmentioning
confidence: 99%